2007
DOI: 10.1017/s0025100307002903
|View full text |Cite
|
Sign up to set email alerts
|

Gemination in Tashlhiyt Berber: an acoustic and articulatory study

Abstract: Tashlhiyt Berber contrasts singletons and geminates in intervocalic as well as in initial and final positions. This study presents results of an investigation of the phonetic correlates that distinguish these types of segments in these three positions. A claim has been made that Tashlhiyt Berber geminates are simple segments that are distinguished from their singleton counterparts primarily by tenseness. This proposal is not supported by our data. The examination of ten temporal and non-temporal parameters sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 22 publications
3
67
1
2
Order By: Relevance
“…As the duration of the acoustic closure of the bilabial increases with consonantal length, the articulatory gestures associated with lip closure can be of longer duration (the compression of the soft lip tissue can continue longer after the occlusion is achieved) and, consequently, of greater extent. Our results are in line with the findings for Japanese, Tarifit Berber, Tashlhiyt Berber, and Moroccan Arabic (Löfqvist, 2006(Löfqvist, , 2007Bouarourou et al, 2008;Ridouane, 2007;Zeroual et al, 2008), where geminates are reported to have longer durations of lip closing compared to singletons. Older articulatory studies on Estonian gemination also show an increasing contact area of the articulatory movements with longer consonants (Eek, 1970a(Eek, , 1970b(Eek, , 1970c(Eek, , 1971a(Eek, , 1971b(Eek, , 1971c.…”
Section: Gesture Characteristic Effect Pɑpi Pipɑ Tɑpi Tipɑsupporting
confidence: 93%
See 1 more Smart Citation
“…As the duration of the acoustic closure of the bilabial increases with consonantal length, the articulatory gestures associated with lip closure can be of longer duration (the compression of the soft lip tissue can continue longer after the occlusion is achieved) and, consequently, of greater extent. Our results are in line with the findings for Japanese, Tarifit Berber, Tashlhiyt Berber, and Moroccan Arabic (Löfqvist, 2006(Löfqvist, , 2007Bouarourou et al, 2008;Ridouane, 2007;Zeroual et al, 2008), where geminates are reported to have longer durations of lip closing compared to singletons. Older articulatory studies on Estonian gemination also show an increasing contact area of the articulatory movements with longer consonants (Eek, 1970a(Eek, , 1970b(Eek, , 1970c(Eek, , 1971a(Eek, , 1971b(Eek, , 1971c.…”
Section: Gesture Characteristic Effect Pɑpi Pipɑ Tɑpi Tipɑsupporting
confidence: 93%
“…Studies focused on consonantal gemination show significantly longer durations of articulatory closure for geminates compared to singletons (e.g., Löfqvist, 2006Löfqvist, , 2007 for Japanese stops, sonorants, and fricatives; Bouarourou et al, 2008 for Tarifit Berber stops and fricatives; Ridouane, 2007 for Tashlhiyt Berber stops; Zeroual et al, 2008 for Moroccan Arabic stops). The movements of relevant articulators to and from the constriction targets for geminates have longer durations than for singletons (Fivela et al, 2007 for Italian stops and sonorants; Zeroual et al, 2008 for Moroccan Arabic stops; Šimko et al, 2014 for Finnish stops).…”
Section: Articulation Of Geminatesmentioning
confidence: 99%
“…This is the primary acoustic distinction between geminates and singletons (Obrecht 1965, Lehtonen 1970, Lahiri & Hankamer 1988, Pickett et al 1999, Aoyama & Reid 2006, Ridouane 2007.…”
Section: Effects Of Consonant Lengthmentioning
confidence: 99%
“…From a phonetic point of view, gemination is mainly manifested as lengthening of the consonant, and consonant duration has been shown to be the major cue for gemination in many languages (e.g., Ghalib 1984;Lahiri and Hankamer 1988;Local and Simpson 1999;Arvaniti 1999Arvaniti , 2001Ham 2001;Hassan 2002Hassan , 2003Ladd and Scobbie 2003;Blevins 2004;Payne 2005;Ridouane 2007). The magnitude of the difference between singleton and geminate consonants varies within and across languages.…”
mentioning
confidence: 99%